D3-lymphadenectomy enhances oncological clearance in patients with right colon cancer. Results of a meta-analysis. Issue 7 (July 2021) - Balciscueta, Zutoia; Balciscueta, Izaskun; Uribe, Natalia; Pellino, Gianluca; Frasson, Matteo; García-Granero, Eduardo; García-Granero, Álvaro
Abstract: Background: D3-Lymphadenectomy, together with complete mesocolic excision (CME), were introduced to provide oncological results after right colon cancer. The aim of this systematic review with meta-analysis was to assess the short and long-term outcomes of right-sided hemicolectomy with CME + D3 as compared with classic right hemicolectomy. Secondary aims included the prevalence of D3-metastasis and skip metastasis when performing CME + D3. Material and methods: A systematic review with meta-analysis was conducted, according to PRISMA methodology. Results: 29 studies were enrolled (2592 patients). No differences were accounted in morbidity variables associated with the measured techniques. CME + D3 was significantly associated with a greater distance between the tumour and the closest vascular tie, a longer colonic resection, a wider resection of mesentery and an increased number of harvested lymph nodes. Regarding to long-terms outcomes, we found a significant decrease in local recurrence in patients undergoing CME + D3 (HR:0.17) and a significant improvement in 3-year and 5-year overall survival rates (HR:0.53 vs. HR:0.57, respectively), as well as an improving survival in patients with stage II and III disease. Overall prevalence of patients with lymphatic metastases in D3-territory was of 8.6% and 2.2% of skip metastases. Conclusions: CME + D3 is a feasible surgical procedure that allows to obtain specimens with higher quality oncological resection, without greater associated morbidity, thus improving survival in patients with stage II and III right colon cancer.